Reduced susceptibility of Malaysian clinical isolates of Burkholderia pseudomallei to ciprofloxacin - Liew, F.Y.; Tay, S.T.; Puthucheary, S.D. (Malaysian Society of Parasitology and Tropical Medicine, 2012)
Ciprofloxacin, a quinolone with good intracellular penetration may possibly be used for treatment of melioidosis caused by Burkholderia pseudomallei, but problems with resistance may be encountered. Amino acid substitutions in gyrA/gyrB have given rise to fluoroquinolone resistance in various microorganisms. Using published primers for gyrA and gyrB, PCR was performed on 11 isolates of B. pseudomallei with varying degrees of sensitivity to ciprofloxacin, followed by DNA sequencing to detect possible mutations. Results showed an absence of any point mutation in either gene. Local isolates have yet to develop full resistance to ciprofloxacin and probably other mechanisms of resistance may have been involved in the decreased sensitivity to ciprofloxacin.